Emotional self-states and coping responses in patients with chronic tinnitus: a schema mode model approach - Boecking, Benjamin; Stoettner, Eva; Brueggemann, Petra; Mazurek, Birgit (Frontiers in Psychiatry, 2024)
Background Amongst “third-wave” cognitive behavioural therapies, schema therapy demonstrates encouraging efficacy across various mental health conditions. Within this field, clinical interest has begun to converge on the “schema-mode-model” – a conceptualization framework for affective, cognitive and behavioral states that guide individuals’ perceptions and behaviours at a given point in time. Schema mode expressions in patients with chronic tinnitus are as-yet unexamined. Methods The present study reports self-report data from N = 696 patients with chronic tinnitus who completed the Schema Mode- and Tinnitus Handicap Inventories alongside measures of perceived stress, anxiety and depression. The Schema Mode Inventory assesses so-called maladaptive “parent”, “child” and “coping” modes. Parent modes can be understood as self-states which are characterized by self-critical and hostile beliefs; child modes are characterized by biographically unmet emotional needs; and coping modes by inflexible attempts to regulate emotion and stabilize one’s sense of self. Descriptive, correlational and mediation analyses investigated schema mode expressions (1) in patients with chronic tinnitus, (2) as compared to published reference values from a healthy control sample, (3) in their relation to other psychological constructs, and (4) regarding their potential role in driving tinnitus-related distress. Results Patients reported mild-to-moderate levels of emotional distress. Compared to healthy controls, patients showed (1) high relative expressions of child-, detachment and compliant coping modes and (2) a conspicuously low relative expression of the ‘punitive parent’ mode. Correlational patterns suggested strong associations of (1) parent as well as angry child modes with perceived stress and anxiety, (2) the vulnerable child mode with all measured constructs and (3) emotional distress with - intrapersonally - emotional detachment as well as - interpersonally - alleged compliance. Mediation analyses demonstrated that tinnitus-related distress was driven by significant interactions between child and coping modes. Conclusions The study provides initial clinical evidence for the relevance and applicability of schema-mode based formulation and treatment planning in patients with chronic tinnitus.